developing Oral Communication Skills In Light Of The Second Generation Curricula- The First Phase Of Primary Education As A Model – - aberkane, nawal; chettouh, zhour (El Omda in Linguistics and Discourse Analysis, 2022)
Teaching Arabic, beginning at the primary stage, aims to provide the learner with the material of daily communication, and to enhance his linguistic balance by developing his communicative language skills; This is reflected in the correct pronunciation, good performance, and good expression; The Arabic language curricula were built through the reforms of the second generation curricula in primary education on this basis. As the teaching of the Arabic language has become based on the following four fields: the field of spoken understanding, the field of oral expression, the field of understanding the written, and the field of written expression. The Arabic language curricula seek through the field of spoken understanding and the field of oral expression to develop the learner's listening and speaking skills, as a basis upon which understanding is built; which represents the key to accessing all learning, and the basis for building efficient communication